Post-Emergence Herbicidal Activity of Nanoatrazine Against Susceptible Weeds - Sousa, Gustavo F. M.; Gomes, Diego G.; Campos, Estefânia V. R.; Oliveira, Jhones L.; Fraceto, Leonardo F.; Stolf-Moreira, Renata; Oliveira, Halley C. (Frontiers in Environmental Science, 2018)
Poly(ɛ-caprolactone) (PCL) nanocapsules have been previously developed as a carrier system for atrazine. However, the efficacy of this nanoformulation against weeds commonly found in crop cultures has not been tested yet. Here, we evaluated the post-emergence herbicidal activity of PCL nanocapsules containing atrazine against Amaranthus viridis (slender amaranth) and Bidens pilosa (hairy beggarticks), in comparison with a commercial formulation of atrazine. For both species, treatment with atrazine-loaded nanocapsules (at 2000 g ha-1) led to a greater decrease in the photosystem II activity (above 50% inhibition relative to the control) than the commercial atrazine formulation at the same concentration (around 40% inhibition). The growth of A. viridis plants was equally reduced by nanoatrazine and commercial formulation (above 64% for root and 75% for shoot). In the case of B. pilosa, atrazine-loaded nanocapsules decreased more effectively the root and shoot growth than the commercial formulation, leading to a loss of plant biomass. Moreover, for both species, the use of ten-fold diluted atrazine-loaded PCL nanocapsules (200 g ha-1) resulted in the same inhibitory effect in root and shoot growth as the commercial formulation at the standard atrazine dose. These results suggest that the utilization of atrazine-containing PCL nanocapsules potentiated the post-emergence control of A. viridis and B. pilosa by the herbicide. Thus, this nanoformulation emerges as an efficient alternative for weed control.